THE REGIONAL DISPARITY BETWEEN THE SOUTH AND THE NORTH OF ITALY - Marta Grycova (European Scientific Journal, ESJ, 2014)
This paper tries to contribute to the research of the problem called Questione Meridionale focusing on the regions with GDP lower than 75% of the EU-27 average. It observes the development of the regional unemployment rate focusing mainly on the period of the recent financial and economic crisis and compares to the development of chosen regional aggregates. The paper tries to answer the questions on the relationships between the regional unemployment rate and GDP per capita, number of violent crimes per 10 000 inhabitants, percentage of employment in High-Tech sectors as a proxy to the investment, percentage of employment in knowledge-intensive services as a proxy to human capital and number of patents applied to European Patent Office as a proxy variable to innovation. This paper uses quantitative methods of research with secondary data from databases. The data series are analyzed and using the methods of comparison and synthesis the recommendations are worked out. The interdisciplinary approach is used in this paper. It draws upon research in regional studies, economic policy, geographical economics and management. The labor market of the regions of Mezzogiorno is much more inflexible than in the northern regions, whose long-term unemployment ratio now approaches the ratio of Mezzogiorno regions as a result of the economic crisis of 2009. The hypotheses about the relationships between the chosen variables are for the majority of monitored regions proved, but with low statistical significance. The highest parameter Beta was calculated for Sicily. So the investment there in High-Tech sectors and knowledge-intensive sectors might have the highest effects.